Role of metals in the selection of antibiotic resistance - Silva, Isabel Alexandre Teixeira da (2020)
The environment is increasingly recognized for its role in the global dissemination of antibiotic resistance - one of the biggest threats to global health. Several non-antibiotic contaminants seem to increase this problem. This study aimed to investigate the role of metals in the selection of antibiotic resistance. To achieve this goal, two strategies were used: 1) an experimental evolution approach and 2) a microcosm-based assay with complex bacterial communities. For this, Escherichia coli ATCC® 25922™ and Aeromonas hydrophila CECT 839T populations were evolved in increasing concentrations of copper and zinc for 80 days and phenotypic and genotypic changes were investigated. Alterations in the tolerance of the evolved populations to other metals was assessed. Antibiotic susceptibility testing by disc diffusion and antibiotic MIC determination were performed. Growth assays were performed to evaluate the effect of metal exposure in bacterial fitness. Genotypic alterations were assessed by rep-PCR. Evolution in the presence of copper or zinc led to an increased tolerance against other metals such as chromium or nickel. Also, E. coli populations evolved with copper increased their MICs for kanamycin, imipenem and sulfamethoxazole; whereas MICs of populations evolved with zinc followed this trend for sulfamethoxazole. Concerning A. hydrophila, populations evolved with copper and zinc increased their MICs for kanamycin. In a few cases, results from disc diffusion tests were inconsistent with MICs determination. Growth assays revealed a fitness cost for E. coli populations evolved with metal, which was not verified for evolved A. hydrophila populations. Severe genotypic alterations were not detected. For the microcosm-based experiment, lab scale microcosms were steed up to confirm selection of antibiotic resistance in aquatic bacterial communities imposed by exposure to copper and zinc for 20 days. Water samples were collected from Antuã river. After metal exposure, colony-forming units were counted in culture media with and without antibiotics. From microcosms exposed to copper and zinc, cefotaxime and kanamycin resistant bacteria were selected and identified. DGGE analyses were performed to assess metal effects in exposed bacterial communities’ structure. Results showed a significant increase in the prevalence of bacteria resistant to cefotaxime and tetracycline in communities exposed to copper; whereas in communities exposed to zinc an increase in bacteria resistant to cefotaxime and kanamycin was verified. Cefotaxime and kanamycin resistant bacteria belonged to genera intrinsically resistant to these compounds, i.e. Pseudomonas spp. and Sphingomonas spp. DGGE profiling revealed that metal exposure altered the structure of bacterial communities while decreasing richness and diversity. This study confirmed that metal exposure induces significant changes in bacterial strains, leading to higher metal and antibiotic tolerance. In aquatic system bacterial communities, metal exposure leads to a higher prevalence of antibiotic-resistant strains.